Sexual Dimorphism of NAFLD in Adults. Focus on Clinical Aspects and Implications for Practice and Translational Research - Lonardo, Amedeo; Suzuki, Ayako (Journal of clinical medicine, 2020)
Nonalcoholic fatty liver disease (NAFLD) embraces the clinico-pathological consequences of hepatic lipotoxicity and is a major public health problem globally. Sexual dimorphism is a definite feature of most human diseases but, under this aspect, NAFLD lags behind other medical fields. Here, we aim at summarizing and critically discussing the most prominent sex differences and gaps in NAFLD in humans, with emphasis on those aspects which are relevant for clinical practice and translational research. Sexual dimorphism of NAFLD is covered with references to the following areas: disease prevalence and risk factors, pathophysiology, comorbidities, natural course and complications. Finally, we also discuss selected gender differences and whether sex-specific lifestyle changes should be adopted to contrast NAFLD in men and women.